Aspects of Algeria’s relations with the Mediterranean countries of Europe through the British newspaper "Courier de l’Europe" between 1776-1791 - Fakair, Abdul Qader (The Algerian Historical Journal, 2026)
This study is a continuation of a previous study published in this magazine )Algerian Historical Magazine( in its previous issue, which dealt with Algerian-Spanish relations through the British newspaper “Courier de l’Europe” between 1776-1791. This time it deals with Algeria's relations with the European Mediterranean countries during the same period, namely Portugal, France, some Italian countries, Malta and Austria, as they have outlets on the Adriatic Sea, which is open to the Mediterranean Sea. The newspaper dealt with many aspects of the relations, including naval confrontations that extended to the Atlantic Ocean, or other aspects such as negotiations to conclude treaties, ransoming prisoners, the issue of paying tributes to the Regency, and news of the spread of the plague in Algiers in 1787, among other events.